2016
DOI: 10.1007/978-1-4614-6669-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Motives of Plant Management and Domestication

Abstract: We analysed the diversity of forms in which human communities of the Tehuacan Valley manage their plant resource, as well as the motivations and factors infl uencing how such management forms are and how intensely held. We explored and identifi ed ecological, sociocultural, economic and technological factors that infl uence how the management forms and their intensity are, as well as the causal relationships between these factors and management decisions. Particularly, the factors mentioned were analysed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…argyrosperma might be associated with cultural preferences regarding fruit and seed selection associated with native American groups. In other domesticated species, genetic structure and morphological differentiation could be associated with fruit selection for a particular morphology (see Aguirre‐Dugua et al., ; Blancas et al., ), and also with differences among human cultural management (Casas et al., ; Blancas et al., ; Sánchez‐de la Vega et al., ). Future morphological and ethnobotanical analyses should be conducted to corroborate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…argyrosperma might be associated with cultural preferences regarding fruit and seed selection associated with native American groups. In other domesticated species, genetic structure and morphological differentiation could be associated with fruit selection for a particular morphology (see Aguirre‐Dugua et al., ; Blancas et al., ), and also with differences among human cultural management (Casas et al., ; Blancas et al., ; Sánchez‐de la Vega et al., ). Future morphological and ethnobotanical analyses should be conducted to corroborate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…), and squashes ( Cucurbita spp. )—have been associated with differences among human cultural management (Casas et al., ; Blancas et al., ; Sánchez‐de la Vega et al., ) and to fruit or seed selection, with favored traits resulting in a particular morphology (Aguirre‐Dugua et al., ; Blancas et al., ). In addition, patterns of genetic structure have been attributed to ecological factors such as elevation gradients in the case of barley and maize (Tanto et al., ; Van Heerwaarden et al., ).…”
mentioning
confidence: 99%
“…Collective regulations importantly influence the management intensity, but differently to that proposed for a general model of management intensity [ 46 ], the highest complexity of such regulations was observed in plants that are only gathered in areas of common access, such as the most valuable medicinal and ceremonial plants. For the contrary, edible species are mainly managed in AFS, where managers have higher control of access to plant resources.…”
Section: Discussionmentioning
confidence: 99%
“…dulcis and A . potatorum ), which indicates a relation between management intensity and the economic role of plants in subsistence [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that landscape elements are valued by farmers according to the roles that they play in the farming strategy [13][14][15][16]. Landscapes are the result of interactions between the natural elements (climate, geomorphology, water, vegetation, fauna), the actors that modify that nature, and the institutional and social context in which these actors are embedded.…”
Section: Introductionmentioning
confidence: 99%